2014
DOI: 10.1038/leu.2014.272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-defined clonal evolution in patients with chronic myeloid leukemia independent of the BCR-ABL status

Abstract: To study clonal evolution in chronic myeloid leukemia (CML), we searched for BCR-ABL-independent gene mutations in both Philadelphia chromosome (Ph)-negative and Ph-positive clones in 29 chronic-phase CML patients by targeted deep sequencing of 25 genes frequently mutated in myeloid disorders. Ph-negative clones were analyzed in 14 patients who developed clonal cytogenetic abnormalities in Ph-negative cells during treatment with tyrosine kinase inhibitors (TKI). Mutations were detected in 6/14 patients (43%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 44 publications
8
94
0
Order By: Relevance
“…38,39 Other mutations were within genes known to be commonly mutated in myeloid disorders including CML such as TP53, KMT2D (MLL2), and TET2. [27][28][29]32,40 Our results clearly indicate that the acquisition of new mutations during TKI therapy was strongly correlated with treatment failure. to TKI therapy (BCR-ABL measured at 0.12% at follow-up), suggesting its presence in a Ph 2 clone as well.…”
Section: Pattern 1: Mutation Persistence After Tki Therapy Does Not Csupporting
confidence: 51%
See 3 more Smart Citations
“…38,39 Other mutations were within genes known to be commonly mutated in myeloid disorders including CML such as TP53, KMT2D (MLL2), and TET2. [27][28][29]32,40 Our results clearly indicate that the acquisition of new mutations during TKI therapy was strongly correlated with treatment failure. to TKI therapy (BCR-ABL measured at 0.12% at follow-up), suggesting its presence in a Ph 2 clone as well.…”
Section: Pattern 1: Mutation Persistence After Tki Therapy Does Not Csupporting
confidence: 51%
“…[42][43][44] Such preleukemic mutations have been reported in other hematologic malignancies but have not been explored in CML extensively. 32,[42][43][44][45][46][47] The present study showed the presence of such mutations in CML patients (16%, 16 of 100 cases) which needs to be confirmed in a larger number of patients and investigated for its clinical relevance. Pattern 1 mutations can be considered indirect evidence of a preleukemic Ph 2 clone from which the leukemic Ph 1 clone evolved (illustrated in Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosine kinase inhibitors (TKIs) suppress the Ph + cell clone, restoring polyclonal hematopoiesis 2 . However, clonal cytogenetic abnormalities in Ph − cells become detectable in some patients achieving a cytogenetic response to TKIs, and slow evolution to myelodysplasia or acute myeloid leukemia (AML) has been observed 2, 3 . In rare cases, identical abnormalities were demonstrated both in Ph + and Ph − cells, but most cases are consistent with independently acquired abnormalities, although an undetected common ancestral event cannot be excluded (reviewed in 4 ).…”
Section: To the Editormentioning
confidence: 99%